Microsporidium Infecting Anopheles superpictus (Diptera: Culicidae) Larvae - Seyed-Mohammad Omrani; Seyedeh-Fatemeh Moosavi; Kourosh Manouchehri (Tehran University of Medical Sciences, 2016)
Background: Microsporidia are known to infect a wide variety of animals including mosquitoes (Diptera: Culicidae). In a recent study on the mosquito fauna of Chahar Mahal and Bakhtiari Province, at the central western part of Iran, a few larvae of Anopheles superpictus were infected with a microsporidium-resembled microorganism. Current investigation deals with the identification of the responsible microorganism at the genus level. Methods: Fresh infected larvae were collected from the field. After determining the species identity they were dissected to extract their infective contents. Wet preparations were checked for general appearance and the size of the pathogenic microorganism. Fixed preparations were stained with Geimsa and Ryan-Blue modified Trichrome techniques to visualize further morphological characters. The obtained light microscopy data were used in the identification process. Results: The infected larvae were bulged by a whitish material filling the involved segments corresponding to a microsporidium infection. Bottle-shaped semioval spores ranged 4.33±0.19×2.67±0.12 and 4.18±0.43×2.45±0.33 micron in wet and fixed preparations, respectively. They were mostly arranged in globular structures comprised of 8 spores. These data was in favor of a species from the genus Parathelohania in the family Ambliosporidae. Conclusion: This is the first report of a microsporidium infection in An. superpictus. The causative agent is diagnosed as a member of the genus Parathelohania. Further identification down to the species level needs to determine its ultrastructural characteristics and the comparative analysis of ss rRNA sequence data. It is also necessary to understand the detail of the components of the transmission cycle.